1993
DOI: 10.1093/nar/21.8.1705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibody-mediated detection of oligonucleotides containing multiple 2,4-dinitrophenyl reporter groups

Abstract: A series of non-nucleoside-based 2,4-dinitrophenyl (DNP) phosphoramidites have been prepared and used in the multiple labelling of oligonucleotides during solid-phase synthesis. The length of spacer arm between the DNP label and the oligonucleotide phosphate backbone, and the number of attached DNP groups have both been varied in order to determine the optimum conditions for anti-DNP antibody binding. Detection using enzyme-linked colorimetric techniques showed sensitivity equivalent to that obtainable using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The 1,2-diol system has been used to construct the non-nucleosidic backbone, the remaining functionality (either amino or the third hydroxy group) being tethered to the conjugate group. Biotinyl (5,10), pyrenyl (6,7), dansyl (DNS) (7), carborane (8), dinitrophenyl (9), phosphotyrosinyl (10), or fluorescenyl (11) residues have been introduced in this manner. It is also possible to keep the remaining functionality appropriately protected during the chain assembly and label it postsynthetically after deprotection (5).…”
Section: Introductionmentioning
confidence: 99%
“…The 1,2-diol system has been used to construct the non-nucleosidic backbone, the remaining functionality (either amino or the third hydroxy group) being tethered to the conjugate group. Biotinyl (5,10), pyrenyl (6,7), dansyl (DNS) (7), carborane (8), dinitrophenyl (9), phosphotyrosinyl (10), or fluorescenyl (11) residues have been introduced in this manner. It is also possible to keep the remaining functionality appropriately protected during the chain assembly and label it postsynthetically after deprotection (5).…”
Section: Introductionmentioning
confidence: 99%
“…reactions. To examine the effect of these reactions, grafting was done using 5′-end Aminolink 2 dT 13 and Aminolink 2 dT 20 . Unfortunately, we were unable to draw any conclusions from this study since no coupling reaction was observed (28).…”
Section: R )mentioning
confidence: 99%
“…One signal amplification strategy is to incorporate multiple reporter groups in oligonucleotide hybridization probes, such as biotin (2-9), fluorophores (7, 10-12), and 2,4-dinitrophenyl (13). The main problems with this strategy, however, are the control of background and an increase in sensitivity that is not very high.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of a standard intercalator 2 and the synthesis of compound 9 (Scheme ) with a terminal hydroxy group for the attachment to the 5‘-end of an oligonucleotide by using phosphoramidite chemistry serve as examples. A similar strategy can be used for the synthesis of analogs of 9 containing a terminal 1,2-diol functionality for linking to the 3‘-end of an oligonucleotide …”
mentioning
confidence: 99%
“…In summary, we have described a practical method for the synthesis of 4-chloro-2-(2-naphthyl)quinoline ( 7 ) and shown that compound 7 is a good substrate for the preparation of triple-helix DNA intercalators. Products, such as 9 , that are compatible with phosphoramidite chemistry can be used in the preparation of triple-helix DNA intercalator−oligonucleotide conjugates. , …”
mentioning
confidence: 99%